2021
DOI: 10.1038/s41565-021-01023-x
|View full text |Cite
|
Sign up to set email alerts
|

Light–matter coupling in large-area van der Waals superlattices

Abstract: Two-dimensional (2D) crystals have renewed opportunities in design and assembly of arti cial lattices without the constraints of epitaxy. However, the lack of thickness control in exfoliated van der Waals (vdW) layers prevents realization of repeat units with high delity. Recent availability of uniform, waferscale samples permits engineering of both electronic and optical dispersions in stacks of disparate 2D layers with multiple repeating units. We present optical dispersion engineering in a superlattice stru… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
86
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(86 citation statements)
references
References 34 publications
0
86
0
Order By: Relevance
“…Recently, the realization of uniform and wafer-scale monolayer TMDs has renewed opportunities in design of van der Waals superlattices [379] . In 2021, Kumar et al reported the experimental realization of square-centimeter-scale, multilayer superlattices with enhanced photoluminescence, which are composed of repeating unit cells of a metal organic CVD grown TMD monolayer (MoS 2 and WS 2 ) and insulating spacers (hBN and Al 2 O 3 ) stacked on the gold backreflector [380] . The emergence of strong coupling in superlattices has been observed at room temperature, and the coupling constants are demonstrated to be tunable by changing the geometric parameters.…”
Section: Extended Monolayersmentioning
confidence: 99%
“…Recently, the realization of uniform and wafer-scale monolayer TMDs has renewed opportunities in design of van der Waals superlattices [379] . In 2021, Kumar et al reported the experimental realization of square-centimeter-scale, multilayer superlattices with enhanced photoluminescence, which are composed of repeating unit cells of a metal organic CVD grown TMD monolayer (MoS 2 and WS 2 ) and insulating spacers (hBN and Al 2 O 3 ) stacked on the gold backreflector [380] . The emergence of strong coupling in superlattices has been observed at room temperature, and the coupling constants are demonstrated to be tunable by changing the geometric parameters.…”
Section: Extended Monolayersmentioning
confidence: 99%
“…The above-mentioned deposition methods (i.e., vacuum filtration, spin coating, and layer-by-layer assembly) and other commonly used thin-film deposition techniques (e.g., spray coating, bar coating, and Langmuir–Blodgett) can successfully generate vdW thin films for electronic device fabrication. In addition to the direct deposition, wet-transfer methods have been utilized for many purposes including changing substrates, transmission electron microscopic analysis, and multilayered heterostructure formation . For the transfer, in general, the poly­(methyl methacrylate) (PMMA) layer is coated on any 2D samples exfoliated/grown on an arbitrary substrate; the substrate is removed by etchant exposure; the PMMA/2D layer is carefully transferred onto a target substrate, and PMMA is removed.…”
Section: Assembly Of Solution-processed Vdw Layered Materialsmentioning
confidence: 99%
“…By coupling ML TMDCs with optical cavities or dielectric photonic crystals (PCs), the half-light half-matter quasiparticles, i.e., exciton-polaritons, will be formed due to the strong exciton-photon interactions 26 28 . However, the atomic thin nature of ML TMDCs (thickness < 1 nm) is nonideal to construct the dielectric resonators by themselves to support optical resonant modes at visible or near-infrared frequencies, due to the limited thickness along the -direction 29 , 30 . Compared to monolayer counterparts, albeit lacking strong luminescence due to the indirect bandgap, multilayer TMDCs still exhibit relatively large exciton oscillator strengths and high refractive indices (>4) 30 .…”
Section: Introductionmentioning
confidence: 99%